2019
DOI: 10.3892/or.2019.6959
|View full text |Cite
|
Sign up to set email alerts
|

XPC inhibition rescues cisplatin resistance via the Akt/mTOR signaling pathway in A549/DDP lung adenocarcinoma cells

Abstract: Xeroderma pigmentosum, complementation group C (XPC) is an accessory recognition gene involved in the nucleotide excision repair (NER) pathway, which is activated during the initial DNA damage recognition stage. It participates in the regulation of DNA damage-induced proliferation and apoptosis. Emerging evidence demonstrates that upregulation of XPC increases the resistance of several tumor cell types to cytotoxic drugs. In addition, it can predict poor patient outcome for non-small cell lung cancer (NSCLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In addition, JAK signaling was involved in the formation of TME by regulating T cell, natural killer (NK), and dendritic cell function (29). Evidence has demonstrated that the mammalian target of rapamycin (mTOR) signaling pathway was associated with metastasis and cisplatin resistance in lung adenocarcinoma (30,31). GO analyses also suggested that the low-risk group was associated with immune-related processes, some of which were negatively regulated, and the results of ESTIMATE analysis showed that the tumor cells in the low-risk group had more immune cell infiltration than those in the highrisk group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JAK signaling was involved in the formation of TME by regulating T cell, natural killer (NK), and dendritic cell function (29). Evidence has demonstrated that the mammalian target of rapamycin (mTOR) signaling pathway was associated with metastasis and cisplatin resistance in lung adenocarcinoma (30,31). GO analyses also suggested that the low-risk group was associated with immune-related processes, some of which were negatively regulated, and the results of ESTIMATE analysis showed that the tumor cells in the low-risk group had more immune cell infiltration than those in the highrisk group.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of lung cancer cells to DDP is a complex process, involving multiple factors and genes, including the mechanisms of the accumulation and deactivation of intracellular drugs, DNA damage repair, autophagy, and apoptosis. [14][15][16][17] Recently more and more research has focused on the mechanism of Delicaflavone in tumors. It exerts antitumor activity by inducing apoptosis and autophagy and Figure 2 Delicaflavone united with DDP regulated lung cancer DDP resistant cells invasion, migration.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of this pathway is considered a latent antitumor therapy . The Akt/mTOR pathway is a critical pathway for LUAD cell proliferation . Through the Akt/mTOR pathway, xeroderma pigmentosum complementation group C repression rescued cisplatin resistance in LUAD cells .…”
Section: Discussionmentioning
confidence: 99%
“…The Akt/mTOR pathway is a critical pathway for LUAD cell proliferation . Through the Akt/mTOR pathway, xeroderma pigmentosum complementation group C repression rescued cisplatin resistance in LUAD cells . However, a few articles reported that STRIP2 was involved in the modulation of the Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%